Адміністративно-правовий статус органів Служби безпеки України - Карпенко, М. М.; Karpenko, M. M. (Вісник Харківського національного університету внутрішніх справ. - 2014. - № 4 (67). - С. 137-148, 2014)
Показано, що адміністративно-правовий статус Служби безпеки України абсолютно повно відображає усі індивідуальні властивості цього правоохоронного органу та його реальне місце у системі правоохоронних органів. З’ясовано, що визначені чинним законодавством права та обов’язки органів Служби безпеки України реалізуються ними в адміністративно-правових відносинах правоохоронної спрямованості. Наголошено, що усі складові адміністративно-правового статусу Служби безпеки України є взаємообумовленими, взаємопов’язаними між собою та взаємозалежними. Зазначені елементи характеризують адміністративноправовий статус Служби безпеки України з точки зору призначення, предметних і функціональних повноважень та особливостей здійснення заходів у сфері забезпечення національної безпеки.

The article aims to clarify the content of administrative and legal status of the Security Service of Ukraine, to define elements that make up its structure and to provide characteristics of each of the proposed elements. It is offered to understand under the administrative and legal status of the Security Service of Ukraine a set of consolidated in the current legislation of Ukraine jurisdictions, powers (rights, duties), guarantees of the activity and liability that allow them to be participants of the administrative and legal relations in the field of guaranteeing the national security of Ukraine. It is found out that the structure of administrative and legal status of the Security Service of Ukraine consists of the target, organizational and jurisdiction units (elements). It also includes guarantees of the activity of the Security Service of Ukraine and liability of its employees. The first element is legally consolidated the aim of formation and tasks of the agency. The second element includes normative regulation of the procedure of the activity of the Security Service of Ukraine, its internal structure, staffing, accountability, etc. The third element consists of a set of powers concerning certain jurisdictions of the Security Service of Ukraine. The content of each of the proposed elements is analyzed. It is grounded that the jurisdiction of the Security Service of Ukraine is determined by a combination of the powers, uniting the rights and duties depending on the feature of their territorial or branch utensils. The author offers to divide the powers of the Security Service according to functional affiliation into information and analytical, counterintelligence, concerning counteraction crime and personal security, concerning realization of operative and search activity, in the sphere of compliance with the state secrets, in the field of border protection and realization of migration policy, in the field of preventing and termination of emergencies and securing the objects of increased safety. It is defined that the specifics of territorial authorities depends on the place of the Security Service of Ukraine within the general management system.

Показано, что административно-правовой статус Службы безопасности Украины абсолютно полно отображает все индивидуальные особенности данного правоохранительного органа и его реальное место в системе правоохранительных органов. Выяснено, что определённые законодательством права и обязанности органов Службы безопасности Украины реализуются ими в административно-правовых отношениях правоохранительной направленности. Подчёркнуто, что все составляющие административно-правового статуса Службы безопасности Украины являются взаимообусловленными, взаимосвязанными между собой и взаимозависимыми. Данные элементы характеризуют административно-правовой статус Службы безопасности Украины с точки зрения предназначения, предметных и функциональных полномочий, а также особенностей осуществления мероприятий в сфере обеспечения национальной безопасности.
Administrative and legal status of the Security Service of Ukraine
Административно-правовой статус органов Службы безопасности Украины
Keywords: адміністративно-правовий статус; Служба безпеки України; повноваження; компетенція; права; обов’язки; гарантії; відповідальність; administrative and legal status; Security Service of Ukraine; powers; jurisdiction; rights; duties; guarantees; liability; административно-правовой статус; Служба безопасности Украины; полномочия; компетенция; обязанности; гарантии; ответственность